Ethnic landscapes in an urban world - Hutchison, Ray; Krase, Jerome (Research in urban sociology, 2007)
This series addresses the major subject areas of urban sociology, ethnic and minority groups within the city, social network of urban residents, location of retail and industrial activities within the metropolitan complex, decline of the central cities and emergence of suburban lifestyles, and the core question of community integration itself. Volume 8 includes case studies from Toronto, Japan, Bulgaria, and other geographic locations with ethnic minority populations. It addresses the major concepts of urban sociology while including perspectives from diverse locations.